2018
DOI: 10.1007/978-981-10-8195-8_10
|View full text |Cite
|
Sign up to set email alerts
|

Development of Hair Fibres

Abstract: The growth of hairs occurs during the anagen phase of the follicle cycle. Hair growth begins with basement membrane-bound stem cells (mother cells) around the dermal papilla neck which continuously bud off daughter cells which further divide as a transient amplifying population. Division ceases as cell line differentiation begins, which entails changes in cell junctions, cell shape and position, and cell-line specific cytoplasmic expression of keratin and trichohyalin. As the differentiating cells migrate up t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 163 publications
2
37
0
Order By: Relevance
“…The GO functional analysis in our study demonstrated that these DMGs were mainly enriched in the classifications of cell structure (e.g., cell projection and plasma membrane) and cell communication (e.g., cytoskeletal protein binding, channel activity and ion channel activity) (Supplementary Figure S4). Cell junctions (GO: 0030054) and cytoskeletal protein binding (GO: 0008092) have been reported to regulate cortex cell movement and reshaping in certain areas of the HF (Morioka et al, 2006;Harland and Plowman, 2018). These results were in agreement with previous reports and verified the importance of intercellular communication during cell reshaping of the HF bulb (Runswick et al, 2001;Arita et al, 2004).…”
Section: Discussionsupporting
confidence: 90%
“…The GO functional analysis in our study demonstrated that these DMGs were mainly enriched in the classifications of cell structure (e.g., cell projection and plasma membrane) and cell communication (e.g., cytoskeletal protein binding, channel activity and ion channel activity) (Supplementary Figure S4). Cell junctions (GO: 0030054) and cytoskeletal protein binding (GO: 0008092) have been reported to regulate cortex cell movement and reshaping in certain areas of the HF (Morioka et al, 2006;Harland and Plowman, 2018). These results were in agreement with previous reports and verified the importance of intercellular communication during cell reshaping of the HF bulb (Runswick et al, 2001;Arita et al, 2004).…”
Section: Discussionsupporting
confidence: 90%
“…During the active hair growth periods, HMK proliferate and cells are ‘pushed’ upwards, whilst undergoing lineage specific differentiation and keratinization. This results in the formation of the three structural compartments of the hair fibre, medulla, cortex and cuticle, the follicle inner root sheath (IRS) that plays a role in the shaping of the hair fibre , and the companion layer . The follicle is encased by the outer root sheath (ORS), which contains stem cells that play an active role in the initiation of the hair growth cycles .…”
Section: The Hair Folliclementioning
confidence: 99%
“…Follicles contain both mesenchymal and epithelial compartments. Hair growth and cornification occurs within the proximal 1-2 mm, a process extensively described in previous studies (Rogers, 2006;Harland, 2018b;Harland & Plowman, 2018;Harland et al, 2019). Briefly, cells from a proximally located and rapidly dividing transient amplifying population migrate distally, then (Auber's line) stop dividing and differentiate into seven phenotypically distinct lineages of keratinocyte, arranged in cylindrical layers, which form the hair shaft and the inner root sheath (IRS) that supports the developing hair ( Fig.…”
Section: Introductionmentioning
confidence: 97%
“…Buried deep under the epidermis, active follicles are elongated cylindrical structures that are approximately 200 µm in diameter and 3-4 mm long with a bulb-like protuberance at their proximal end. They are surrounded by a thick network of collagen fibrils within which are embedded blood vessels, fibroblasts, neurons and adipocytes (Harland, 2018a;Harland & Plowman, 2018). Follicles contain both mesenchymal and epithelial compartments.…”
Section: Introductionmentioning
confidence: 99%